Fuel and Food Price Subsidies : Issues and Reform Options. (Policy Papers; Policy Paper ;, 2008)
Government price subsidies are pervasive in developed, emerging, and low-income countries. A subsidy is a form of government intervention resulting in a deviation of an actual price facing consumers and producers from a specified benchmark price. Subsidies affect consumption and production patterns as well as the distribution of resources, with important implications for the budget, expenditure composition, and long-term growth. They can and often do involve fiscal costs, but not all affect government fiscal accounts in the same way. Price subsidies have spillover effects onto prices and quantities in domestic, regional, or global markets. This paper discusses the key issues and policy options in the reform of subsidies for fossil fuels and selected food commodities, and their implications for the work of the Fund.